The potential impact of agricultural activities on water quality of Bera lake - Nor Suhada, Abdul Zaman (2018)
The thesis is about the research on the water quality due to agricultural activities. One of the agricultural activities that active in Bera Lake is palm oil plantation. Agricultural activities cause the pollution to water. During the research, water samples were taken two times to know about the pollution of water at Bera Lake. The study was conducted at three sampling stations which were at agricultural site, resort, and jetty area. All of the sampling stations were around Bera Lake. A total of thirteen water quality parameters were analyzed including in situ test and laboratory analysis. For in-situ test, the data were collected directly using equipment while for the laboratory test, standard methods and procedures were carried out to collect the data. All the parameters were classified according to Department of Environment Water Quality Index (WQI) Malaysia and National Water Quality Standards (NWQS) Malaysia. The physicochemical parameters were temperature, pH, electrical conductivity (EC), dissolved oxygen (DO), turbidity, biochemical oxygen demand (BOD), chemical oxygen demand (COD), total suspended solids (TSS), total dissolved solids (TDS), ammoniacal nitrogen (NH3-N), nitrate (NO3-), and phosphate (PO43-). Based on the results, the highest BOD was at agricultural site (6.73mg/L) and the lowest BOD was at resort (2.35mg/L) while the highest COD was at jetty area (14.59mg/L) and the lowest COD was at agricultural site (10.40mg/L). For dissolved oxygen, the highest dissolved oxygen was at agricultural site (4.50mg/L) and the lowest dissolved oxygen was at resort (4.09mg/L). Based on the results, it showed that the water quality of Bera Lake was in Class II based on the Water Quality Index (WQI) Malaysia and was categorized in clean water.